Systematic Literature Review: Kemampuan Menulis Matematis dan Resiliensi Matematis 2019-2023 - Arvianti, Kharisa Rahma (Jurnal Pendidikan Matematika, 2024)
Mathematical writing ability significantly impacts students' learning success as it reflects the depth of their understanding of the learning material. Students demonstrating a high level of mathematical resilience can tackle complex issues and obstacles in mathematics learning. The aim of this research is to describe the theoretical framework in studies related to mathematical writing ability and mathematical resilience from 2019 to 2023, as well as to depict trends related to research on mathematical writing ability and mathematical resilience during this period. The research utilizes the Systematic Literature Review (SLR) method by examining 17 relevant articles. The findings reveal various definitions and indicators collected in the research. Three dominant indicators are used in studies on mathematical writing ability, and six indicators according to Sumarmo are employed in research on mathematical resilience. Trends in related research tend towards qualitative research types, particularly at the junior high school and high school education levels.